Implementasi Penguatan Profil Pelajar Pancasila di Sekolah Menengah Atas - Safi’i, Imam; Subali, Subali; Ahmad, Zuhad; Ghozali, Muhammad Zulfa Azhari; Sobri, Sobri (Universitas Mathla'ul Anwar Banten, 2023)
This study aims to describe the forms of implementing the project values of strengthening the Pancasila student profile in one of the private high schools in Jakarta. The method used is observation, namely through direct observation of the research object accompanied by interviews to collect data more comprehensively. The results of the study show that the values of the Pancasila student profile have been implemented intensively at SMA Muhammadiyah 18 Jakarta. The profile of faith, piety to God Almighty and noble character is implemented through the activities of carrying out congregational prayers, reciting and studying the Al Quran. The global diversity profile is implemented through discussions and studies of various foreign cultures. The mutual cooperation profile is implemented through community service activities, group discussions, and the preparation of the OSIS work program. The independent profile is implemented through completing daily assignments, administering exams, and returning and tidying up books in the library. The creative profile is implemented by cultivating students to create new things, carrying out entrepreneurial activities in the form of selling cakes during recess, turning used goods into art, and helping UMKM part time. Critical reasoning is implemented through activities to accustom students to asking questions in class, discussing, giving arguments on the problems posed, criticizing and respecting differences of opinion. The results of this study can be used as a model in implementing Pancasila student profiles in high school.